(untitled) (Research, Society and Development, 2022)
Objective: culturally adapt the Bogardus Social Distance Scale in the domains of schizophrenia and heroin addiction to Portuguese spoken in Brazil. Method: this methodological study was developed through the process of cultural adaptation: 1) translation; 2) committee of judges; 3) back translation; 4) pre-test; and 5) balancing the scores. In the pre-test phase, the population sample consisted of 40 health professionals from Primary Health Care. Results: the scale adapted to Brazilian Portuguese was evaluated as equivalent to the original instrument. For better cultural approximation to the Brazilian reality, the domain “heroin dependence” was changed to “cocaine dependence”. Cronbach’s alpha value was 0.69 and 0.62 for the schizophrenia and cocaine dependence domains, respectively, indicating that there was semantic, cultural and conceptual equivalence in the adapted instrument. Final considerations: the cultural adaptation of the scale obtained representative results of good internal consistency, but there is a need to validate this instrument through the analysis of psychometric properties.